The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/sdi.12924
|View full text |Cite
|
Sign up to set email alerts
|

Achieving dialysis adequacy: A global perspective

Abstract: Attempts to quantify the performance of dialysis therapy had started even before maintenance dialysis became widely available. Initial efforts in 1950s were centered around measuring the ability of a dialyzer to remove the solute mass, leading to coinage of the terms "clearance" and "dialysance". 1 The concept of adequacy, or the understanding that patient outcome was linked to performance of dialyzer, gathered pace in the 1970s on the basis of work by Babb and Scribner (square-meter hour hypothesis), Kopp (li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…So the need for dialysis will increase over time. However, there is a lack of information about the number of dialysis patients in Uttarakhand state [4]. Caregivers often receive little attention, and the main focus has remained on the patients.…”
Section: Introductionmentioning
confidence: 99%
“…So the need for dialysis will increase over time. However, there is a lack of information about the number of dialysis patients in Uttarakhand state [4]. Caregivers often receive little attention, and the main focus has remained on the patients.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of frailty increases with age and can reach 21.5% among the elderly in China [ 14 ]. Dialysis adequacy refers to the removal of excess water and toxins from the patient's body through HD to reach a comfortable state [ 15 ]. In a domestic study involving 120 MHD patients, dialysis adequacy was tested, and it was found that MHD patients with more adequate dialysis (i.e., urea clearance index ≥1.2) had a lower probability of muscle content decline and were less prone to frailty [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, malnutrition and sarcopenia are common complications in MHD patients. Evidence has shown that MHD patients with hypoproteinemia are more susceptible to frailty, and the SA level is negatively correlated with the degree of frailty [ 15 ]. Another study holds that sarcopenia is the core mechanism of frailty, and GS, WS, and MAMC are important indexes to diagnose and evaluate sarcopenia [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 1 The efficacy of HD is closely associated with patient survival time and quality of life. 2 , 3 The urea clearance index (Kt/V, where K = dialyzer clearance of urea, t = dialysis time, and V = volume of distribution of urea) and urea reduction rate (URR) are the 2 most important indices for evaluating the adequacy of dialysis. 3 , 4 These calculations are based on blood urea nitrogen (BUN) concentrations taken before and after dialysis.…”
Section: Introductionmentioning
confidence: 99%
“… 2 , 3 The urea clearance index (Kt/V, where K = dialyzer clearance of urea, t = dialysis time, and V = volume of distribution of urea) and urea reduction rate (URR) are the 2 most important indices for evaluating the adequacy of dialysis. 3 , 4 These calculations are based on blood urea nitrogen (BUN) concentrations taken before and after dialysis. The classical method (CLM) of obtaining these values, based on the second-generation Daugirdas formula, 5 , 6 is the most widely used method in clinical practice.…”
Section: Introductionmentioning
confidence: 99%